Digitalisasi Layanan E-Legalisir Sebagai Upaya Peningkatan Pelayanan Legalisir Ijazah dan Transkip Nilai di Politeknik Negeri Sriwijaya - Ade Wati; Ravie Laday; Ulfah Muharramah; Velicya Khusnul (Jurnal Komputer, Informasi dan Teknologi, 2026)
The legalization of diplomas and academic transcripts is a vital administrative service in higher education to ensure document authenticity for further study, employment, and other official purposes. However, manual legalization processes are often time-consuming, inefficient, and vulnerable to document loss and weak verification. Advances in information technology enable digital solutions such as electronic signatures, QR codes, and digital certificates, supported by Indonesia’s legal framework on electronic documents. This study aims to design and develop a web-based E-Legalization system to improve service efficiency, enhance document security and authenticity, and ensure legal compliance. The proposed system is expected to provide a faster, more secure, and easily accessible digital legalization service, supporting the development of a sustainable digital campus ecosystem.